2013
DOI: 10.1159/000351968
|View full text |Cite
|
Sign up to set email alerts
|

Previous Open Renal Surgery Increased Vascular Complications in Percutaneous Nephrolithotomy (PCNL) Compared with Primary and Secondary PCNL and Extracorporeal Shock Wave Lithotripsy Patients: A Retrospective Study

Abstract: Objective: To evaluate the vascular complications of percutaneous nephrolithotomy (PCNL) patients who have undergone previous open surgery, PCNL and extracorporeal shock wave lithotripsy (ESWL). Patients and Methods: 360 patients who underwent a PCNL procedure were included into the study. The patients were divided into 4 groups: group 1: primary PCNL (n = 232); group 2: previous open nephrolithotomy (n = 42); group 3: previous PCNL (n = 33); group 4: previous ESWL (n = 63). The periods of operation and fluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 14 publications
0
15
2
1
Order By: Relevance
“…Also Yesil et al and Khoromi et al did not demonstrate any affect of previous renal surgery on hospitalization period after PNL [11,23]. In this study hospitalization period was longer in patients with history of open renal surgery but statistical analysis revealed no significant difference between groups (p 0.506).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Also Yesil et al and Khoromi et al did not demonstrate any affect of previous renal surgery on hospitalization period after PNL [11,23]. In this study hospitalization period was longer in patients with history of open renal surgery but statistical analysis revealed no significant difference between groups (p 0.506).…”
Section: Discussioncontrasting
confidence: 45%
“…Although, Yesil et al compared patients in four groups as PNL after open renal surgery, primary PNL, secondary PNL and PNL after shock wave lithotripsy, they evaluated only vascular complications [11]. Additionally, this study included the largest patient number who underwent PNL with previous open renal surgery (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…15 Sofikerim et al and Kurtulus et al did not report any unfavourable effect of previous ORSS on hospitalization time after PNL; however, their hospitalization times were much longer when compared with Yesil's study (4.4 vs. 4.2 days and 3.7 vs. 3.3 days, respectively). 12,14 In the current study, we have not found any statistically significant difference in hospitalization time between patients with previous open nephrolithotomy and previous open pyelolithotomy surgery (p=0.820).…”
Section: Discussionmentioning
confidence: 75%
“…Said et al (8), however, stated that previous open surgery can be an important determinant for hemorrhage and transfusion requirement in PNL. Yesil et al (9) reported that severe hemorrhages requiring angioembolization were frequent in their 42 patients who underwent open renal surgery. Sofikerim et al (10) determined that the incidence of bleeding requiring transfusion was nearly twice as high in the group with open surgery, suggesting that this was a predisposing factor for bleeding complication.…”
Section: Discussionmentioning
confidence: 99%